THE USE OF ENGLISH FOR TOURISM IMAGE AND BRANDING - Widya Rizky Pratiwi; Juhana Juhana; Lukytta Gusti Acfira (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
Using English for tourism branding and promotion in Indonesia effectively enhances Indonesia's appeal as a tourist destination. This study aimed to investigate the use of English for tourism branding and promotion in Indonesia. It was qualitative research with a case study approach involving domestic and international visitors and local communities as informants. The data collection method was questionnaire distribution, semi-structured interviews, observations, and photos. In analyzing the data, the researcher conducted 6 steps from preparing raw data (transcripts, field notes, images, etc.), organizing and preparing data for analysis, reading all data, coding data (themes or descriptions) by hand or computer, linking themes/descriptions, and then interpret its meaning from the theme/description. The findings presented that participants tried to use English in tourism objects to practice their English language skills, to improve speaking confidence, and to provide the best service for tourism image and branding. However, Indonesian people face some problems when speaking, resulting in a limited selection of sentences like "How are you." The challeges were solved by involving smartphone-based technology, such as Google Translate platform when communicating. This study may contribute to the acceleration of Second Language Acquisition (SLA) and encounters an impact on boosting proficiency in English as a foreign language, especially for enhancing speaking, which encouraged tourism growth in Indonesia